Cognitive Reappraisal and the Association Between Perceived Stress and Anxiety Symptoms in COVID-19 Isolated People - Xu, Chen; Xu, Yanjun; Xu, Song; Zhang, Qianhui; Liu, Xiaotong; Shao, Yifan; Xu, Xiaoxiao; Peng, Li; Li, Min (Frontiers in Psychiatry, 2020)
The purpose of this study is to examine how the emotion regulation strategy, cognitive reappraisal, affects the association between perceived stress and anxiety symptoms in COVID-19 isolated people. Data for this cross-sectional study come from a community-based online survey of COVID-19 isolated people (N = 328), who are not infected with the 2019-nCoV virus. We applied correlation and regression for data analysis, and found that cognitive reappraisal negatively moderated the relationship between perceived stress and anxiety symptoms. These results give us a new perspective on understanding the relationship between anxiety symptoms and perceived stress by clarifying the protective function of cognitive reappraisal. It buffers the induced negative emotion when COVID-19 isolated people perceive overpressure, and thus instigates future research into targeted clinical interventions, which aim to cultivate cognitive reappraisal skills for those isolated people in the face of stressful events or crisis events.